2016
DOI: 10.5456/wpll.18.3.7
|View full text |Cite
|
Sign up to set email alerts
|

'Diversity' 'Widening Participation' and 'Inclusion' in Higher Education: An International study

Abstract: There is a danger of diversity becoming a corporate buzzword. […] Rightly or wrongly you get fed up of hearing it. I don't think it's bad for anyone to strive for diversity for whatever reason, diversity in my opinion is a good thingbut maybe companies are only striving for it because it makes them look good and it's in danger of becoming just another word they can add to their website.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
1
16
0
3
Order By: Relevance
“…This diversity rhetoric often reduces individuals to group-based categories associated with specific strengths and qualities (Litvin, 1997). A binary is then created in the context of this rhetoric between traditional and non-traditional students (Gibson, et al, 2016). Individuals are positioned as 'exemplars of particular demographic categories' (Litvin, 1997: 204) and placed in crude, simplistic group-based prototypes (Lorbiecki & Jack, 2000) that do not recognise the complexity of their lives and identities (Thompson, 2019).…”
Section: Widening Participation In Elite Universitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This diversity rhetoric often reduces individuals to group-based categories associated with specific strengths and qualities (Litvin, 1997). A binary is then created in the context of this rhetoric between traditional and non-traditional students (Gibson, et al, 2016). Individuals are positioned as 'exemplars of particular demographic categories' (Litvin, 1997: 204) and placed in crude, simplistic group-based prototypes (Lorbiecki & Jack, 2000) that do not recognise the complexity of their lives and identities (Thompson, 2019).…”
Section: Widening Participation In Elite Universitiesmentioning
confidence: 99%
“…The twenty English Russell Group universities responded to increased government pressure to widen access by committing £265 million to widening participation activities in the 2019/20 academic year (Russell Group, 2019). However, elite universities have been criticized for adopting a 'deficit approach' in their discourse around diversity and inclusion and hence towards students recruited through such schemes (Archer, 2007;Thompson, 2019), and viewing them as lacking the required academic skills and attributes (Archer, 2007;Gibson et al, 2016;McLellan, Pettigrew & Sperlinger, 2016). Research has shown that some WP students who enter elite institutions feel 'out of place' in academic, social and recreational spaces (Reay, Crozier & Clayton, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst research by Bromley and Powell (2012) demonstrated how student activism can change the practices of educational institutions to better meet the needs of students, Blair and Valdez Noel (2014) found little evidence to show that student evaluations actually lead to real change. This project seeks real change and greater student success and retention in an environment that Gibson et al (2016) describe as entrenched in practices that do not empower or widely consult students.…”
Section: Advocacy Student Partnership and Student Voice In Australiamentioning
confidence: 99%
“…We also know that requiring them to identify themselves using terms with which they do not feel comfortable affects their experience of higher education [8,9], and that challenges in communication and administrative procedures can have a range of negative impacts on students [10]. Alongside this, Gibson et al, (2016), show how labelling students can pathologise them, setting them aside as distinct to the rest of the student population [11]. They argue that institutions need to be proactive in their engagement with the students as key stakeholders in the process, where they currently often excluded.…”
Section: Introductionmentioning
confidence: 99%